Land behind Baghdad. A History of Settlement on the Diyala Plains - Adams, Robert McC. (1965)
Part 1: The Contemporary Setting (1. Major Natural Variables: Climate, Flora and Fauna, Land and Water; 2. Basic Patterns of Agricultural Subsistence; 3. Recent Trends in Settlement). Part 2: The Changing Patterns of Ancient Occupance (spez. 4. The Formation of Walled Towns, 4000-2100 B.C.; 5. Regional Autonomy, Subjugation, and Decline, 2100-626 B.C.). Appendixes: A. Methods of Topographic Archaeology; B. Ceramic Dating Criteria for Surface Reconnaissance; С. Register of Archaeological Sites in the Diyala Region (locates and describes briefly 867 sites).